Reactions of selected parents toward the trade courses offered at the Hadji Butu School of Arts and Trades - Abdulla, Utumama 1923- (s.n.], 1965)
This study determined the reactions of selected parents toward the trade courses offered at the Hadji Butu School of Arts and Trades. The adequacy of the trade courses offered in meeting the needs of the community and the availability of the raw materials in the community which are utilized in the trade courses were also determined.